The “Ecological Niche-Carrying Capacity” Crisis and Symbiotic Pathways of Primary Education Programs in Higher Vocational Colleges under the Context of Population Decline: A Structural Reflection from the Perspective of Educational Ecology - HanFang (Journal of Exploration of Vocational Education, 2025)
Against the backdrop of China’s unprecedented population decline, this paper employs educational-ecology theory to examine the “niche–carrying-capacity” crisis confronting primary-education programmes in higher-vocational colleges (HVCs). Using literature review and conceptual analysis, the study finds that falling birth rates have shrunk the social niche for these programmes while simultaneously over-loading their institutional carrying capacity, resulting in enrolment shortages, resource waste and curricular mismatch. To restore ecosystem balance, the paper proposes three symbiotic pathways: (1) re-niching through interdisciplinary curriculum expansion (early-childhood, educational-technology and psychology tracks); (2) optimising carrying capacity via resource-sharing, blended learning and flexible class-size policies; and (3) enhancing adaptive fitness by deepening school–enterprise cooperation, practice-based training and localized graduate-output agreements. The ecological lens reveals that sustainable survival depends on continuous co-evolution with demographic, labour-market and policy sub-systems. Limitations and directions for empirical, interdisciplinary and regional longitudinal studies are discussed.